2018
DOI: 10.1177/2513850217748501
|View full text |Cite
|
Sign up to set email alerts
|

What makes learning Chinese characters difficult? The voice of students from English secondary schools

Abstract: This study initially investigated the beliefs of beginner learners of Chinese as a foreign language (CFL) about the difficulties of learning Chinese and how they can overcome the difficulties they encounter. Pupils (179) from two state secondary schools in England responded to a Likert scale questionnaire and shared their views in interviews. Surprisingly, pupils think that character recognition is more difficult than their production. They also showed their concern about homophones in Chinese and the lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Based on related research (e.g., Chen, 2016;Liu, 2009;Luo, 2014;Spencer, 2015, Weber, 2017Yang, 2018), two questionnaires were developed, one for learners and one for curriculum designers. The questionnaire items were on a 5-point Likert scale (from Strongly Agree = 5 to Strongly Disagree = 1) and were designed to measure participants' views.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Based on related research (e.g., Chen, 2016;Liu, 2009;Luo, 2014;Spencer, 2015, Weber, 2017Yang, 2018), two questionnaires were developed, one for learners and one for curriculum designers. The questionnaire items were on a 5-point Likert scale (from Strongly Agree = 5 to Strongly Disagree = 1) and were designed to measure participants' views.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Studies on learners' beliefs about Chinese language learning have suggested that most learners consider writing characters the most challenging aspect (Ye, 2013). A recent study by Yang (2018) explored learners' beliefs about the importance of learning Chinese characters and their learning strategies. This study found that although young English-speaking teenagers considered writing Chinese characters more difficult than recognizing them, they thought it was worth spending time learning to write.…”
Section: Learner Belief About L2 Chinese Character Learningmentioning
confidence: 99%
“…Regarding character learning strategies, learners agreed that handwriting and using radicals were effective strategies for memorizing characters. However, Yang (2018) only investigated five strategies and did not further explore the relationship between learners' beliefs and strategy use in Chinese character learning. The questions of whether and how learners' beliefs about Chinese character learning influence their learning strategies remain unanswered.…”
Section: Learner Belief About L2 Chinese Character Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Chinese, the only existing pictographic language in the modern world, is one of the most difficult languages to learn [16], [17]. There are more than 200,000 commonly used words in Chinese that are composed of 5,000 characters.…”
Section: Introductionmentioning
confidence: 99%